Privacy Mediation for Child Digital Literacy: Building Surveillance Awareness for Society - Seabra, Antony; Cavalcante, Claudio; Lifschitz, Sergio (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Children and adolescents increasingly interact with mobile applications that silently exchange personal information with multiple analytics, advertising, and tracking services, often within broader digital environments that may also expose them to profiling, manipulation, and other forms of online risks. Because these data flows remain largely invisible to non-specialists, young users and their caregivers are often unable to recognize how everyday app usage may expose minors to these persistent forms of digital surveillance. In this paper, we propose a Privacy Mediation Architecture that transforms mobile network observations into semantically meaningful and user-interpretable privacy explanations. Designed particularly for contexts involving minors, the architecture aims to support digital literacy by making hidden surveillance practices understandable to children, adolescents, and their caregivers. An exploratory evaluation with parent-child pairs indicates that semantically mediated explanations may improve users’ understanding of otherwise opaque mobile data collection behaviors, reinforcing transparency and explanation as mechanisms for privacy awareness and informed decision-making.